A new species of the genus Scolopsis Cuvier, 1830 (Perciformes: Nemipteridae) from southern India and Sri Lanka - Mishra, S. S.; Biswas, Sudeepta; Russell, Barry C.; Satpathy, K. K.; Selvanayagam, M. (Zootaxa, 2013)
Scolopsis igcarensis, a new species of monocle bream (family Nemipteridae) from the coastal waters of southern India and Sri Lanka is described. The species is distinguished from other species of the genus Scolopsis by a combination of the following characters: scales on top of head reaching forward to between anterior nostril and snout tip; lower margin of eye below the line from snout tip to upper pectoral fin base; a bony ridge below eye; a white band from behind eye to level of end of dorsal fin base.